Identification of comorbid conditions among middle school students: A cross-sectional study of Jammu province - Khan, Rafia; Mittu, Harish (Journal of Interdisciplinary Studies in Education, 2024)
Using a multistage sampling technique, the students completed the self-constructed Identification Battery on Comorbid Conditions (IBCC), which assesses 10 disorders, including dyslexia, dysgraphia, dyscalculia, dysphasia, dyspraxia, anxiety, attention deficit hyperactive disorder (ADHD), obsessive‒compulsive disorder (OCD), autism, and tic disorder. The results revealed that 20.66% of the students exhibited comorbid conditions, with dyscalculia being the most prevalent, followed by dyslexia and others. Comorbid conditions varied, with some students having different combinations of disorders. The Jammu district had the highest prevalence. This study emphasizes the importance of early diagnosis and intervention, highlighting the need for increased stakeholder awareness to address these issues effectively